Pembelajaran Diferensiasi dengan Metode Discovery Learning dikaji dari Motivasi Belajar Materi Sel di SMP - Fitriyanis (Dinas Pendidikan dan Kebudayaan Kabupaten Kubu Raya Provinsi Kalimantan Barat, 2024)
Understanding the concepts in science learning is very important for students to master because they have deep meaning for appreciating life. Students' understanding of cell material is still low because this material tends to be abstract and there are many Latin terms that are foreign and difficult for students, so a learning approach is needed that can meet students' needs in studying this material. This research aims to describe the implementation of differentiation learning using the Discovery Learning method and its impact on student learning motivation in cell material in class 8A of SMPN 2 Sungai Raya. The research approach used is qualitative with a case study design. Data was collected through observation, interviews and questionnaires filled out by 39 students. The research results show that differentiation learning using the Discovery Learning method can increase students' learning motivation. Indicators of increased learning motivation can be seen from persistence, active participation in learning, and increased students' cognitive and affective abilities. With a variety of activities and media used, students can enjoy a fun and meaningful learning experience. Differentiated learning using the discovery learning method can be used as an effective strategy to increase student learning motivation. Teachers need to map students' learning needs and adjust the learning methods used to suit students' learning styles and interests.